SPATIOTEMPORAL DISTRIBUTION OF THE CONGLOMERATE RESERVOIR JATIBARANG FORMATION, MELANDONG FIELD, NORTH-WEST JAVA BASIN, INDONESIA - Adhari, Muhammad Ridha; Nirwana, Akmal Muhni; Gunarsih, Dina (Indonesian Physical Review, 2023)
Subsurface mapping of the distribution of the reservoir is essential to be conducted in order to minimize many risks such as financial losses and also to increase profit from hydrocarbon production. This research was conducted on the Jatibarang conglomerate reservoir in Melandong Field, North West Java Basin, Indonesia. There are three objectives of this study which are to perform elastic impedance (EI) seismic inversion using available 3D seismic data, to determine the most suitable elastic impedance angle for the data, and to map spatiotemporal distribution of the Jatibarang Formation reservoir in the Melandong field, North West Java basin, Indonesia. EI inversion was selected for this study using the inversion angle ranging from the near stack (5º-15º) to the far stack (20º-30º). Results from this study show that EI seismic inversion can help in detecting the distribution of the lithology and hydrocarbon within the target zone. Angle 5º is considered as the best EI angle for the studied data as indicated by a correlation value of 0.65. Moreover, EI angles 15º and 10º are less reliable as shown by their correlation value of 0.6 and 0.56, respectively. These results are expected to provide some new insights into the distribution of the Jatibarang reservoir, and help in exploration, exploitation, and development of oil and gas fields in Melandong Field, North West Java Basin, Indonesia.